2013
DOI: 10.1039/c3cp51108a
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating dynamics with chemical structure: probing vibrationally-enhanced tunnelling in photoexcited catechol

Abstract: Ultrafast time-resolved velocity map ion imaging (TR-VMI) and time-resolved ion-yield (TR-IY) methods are utilised to reveal a comprehensive picture of the electronic state relaxation dynamics in photoexcited catechol (1,2-dihydroxybenzene). After excitation to the S1 ((1)ππ*) state between 280.5 (the S1 origin band, S1(v = 0)) to 243 nm, the population in this state is observed to decay through coupling onto the S2 ((1)πσ*) state, which is dissociative with respect to the non-hydrogen bonded 'free' O-H bond (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
90
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(112 citation statements)
references
References 66 publications
20
90
2
Order By: Relevance
“…Studies on substituted phenols have also shown the quite dramatic effect substituents have on the topography of either the S1 or S2 (or both) potential energy surface (PES), resulting in noticeable effects on the S1/S2 tunneling probability and hence S1 lifetime. [17][18]21,45,46 Similar effects on the local topography of the S1 or S2 PESs from a weakly perturbing solvent will undoubtedly have a similar effect on the S1 lifetime as observed here. Whilst the gas-phase studies compare favorably with those in the non-polar cyclohexane, as expected, this is not the case in acetonitrile (r = 37.5).…”
Section: The Gas-versus Solution-phase Studiessupporting
confidence: 52%
See 4 more Smart Citations
“…Studies on substituted phenols have also shown the quite dramatic effect substituents have on the topography of either the S1 or S2 (or both) potential energy surface (PES), resulting in noticeable effects on the S1/S2 tunneling probability and hence S1 lifetime. [17][18]21,45,46 Similar effects on the local topography of the S1 or S2 PESs from a weakly perturbing solvent will undoubtedly have a similar effect on the S1 lifetime as observed here. Whilst the gas-phase studies compare favorably with those in the non-polar cyclohexane, as expected, this is not the case in acetonitrile (r = 37.5).…”
Section: The Gas-versus Solution-phase Studiessupporting
confidence: 52%
“…Cursory inspection of the 4-TBC + parent transient relative to the corresponding H + transient reveals that the S1 state decays on a similar timescale to the appearance of H-atoms associated with O-H dissociation. Indeed, fitting this transient with a bi-exponential decay function (purple line) returns time constants of g τIVR(H) = 0.4 ± 0.1 ps, associated with rapid intramolecular vibrational energy redistribution (IVR) in the S1 state as seen in our previous investigation, 21 and g τP + = 4.9 ± 0.6 ps, which is assigned to excited state population flux from the S1 state, the P + signifying decay of the non-deuterated isotopologue parent ion signal (and therefore S1 state population). Importantly, this shows a clear correlation to the appearance time of H + .…”
Section: Results and Discussion A Gas-phase Studiesmentioning
confidence: 99%
See 3 more Smart Citations